1987
DOI: 10.3171/jns.1987.66.3.0400
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration following spinal cord injury

Abstract: The results are presented of a prospective study of the course of 283 spinal cord-injured patients who were consecutively admitted to five trauma centers participating in the Comprehensive Central Nervous System Injury Centers' program of the National Institutes of Health. Of the 283 patients, 14 deteriorated neurologically during acute hospital management. In 12 of the 14, the decline in neurological function could be associated with a specific management event, and in nine of these 12 the injury involved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(78 citation statements)
references
References 8 publications
3
72
0
3
Order By: Relevance
“…15 There is conflicting evidence regarding the timing of surgery of SCI patients, and the related complication rate and LOS. Marshall et al 16 reported in 1987 that postoperative neurological deterioration appeared only in cervical SCI patients who were operated early (5 days or less after injury). This report made some surgeons shy away from early surgery in patients with traumatic SCI.…”
Section: Comparison Between Sci and Non-sci Trauma Centers A Ploumis mentioning
confidence: 99%
“…15 There is conflicting evidence regarding the timing of surgery of SCI patients, and the related complication rate and LOS. Marshall et al 16 reported in 1987 that postoperative neurological deterioration appeared only in cervical SCI patients who were operated early (5 days or less after injury). This report made some surgeons shy away from early surgery in patients with traumatic SCI.…”
Section: Comparison Between Sci and Non-sci Trauma Centers A Ploumis mentioning
confidence: 99%
“…In acute systemic trauma, there is a greater probability of failure of alignment and fusion, and surgical treatment may be precluded by the lack of specific equipment and experienced personnel. 21,22 Furthermore, definitive and unequivocal evidence to support the practice of early or late surgery are still lacking in clinical studies. 21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Recently, in an evidence-based review of the literature, Fehlings and Tator 10 concluded, on the bases of the current knowledge, that early decompression can be considered a practice option.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many reports have documented that hemorrhage, microvascular infarction, spasm, spinal cord edema, and free radical production are relevant factors affecting this serious condition. 7,8 Lu et al 9 reported the predictable risk factors for delayed apnea following middle to lower CSCI in the presence of diffuse and extensive cord lesions, respiratory distress, and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although the mechanism causing spinal deterioration is still unclear, a structural instability in the injured segment is one of the most important factors affecting these detrimental changes. 3 Surgical decompression and fixation of the cervical spine is the recommended treatment in a patient with structural damage, such as a spinal fracture-dislocation.…”
Section: Introductionmentioning
confidence: 99%